U.S. tight oil supply flexibility: A multivariate dynamic model for production and rig activity - Halvor Briseid Storrøsten (Statistics Norway, Research Department, 2023)
This paper examines the supply of U.S. LTO from both a theoretical and empirical point of view. The theory model combines endogenous rig activity and stylized reservoir pressure mechanics with the classic Hotelling model for exhaustible resource extraction. The empirical section presents a vector error correction model for U.S. LTO production. Both models allow for simultaneous modeling of U.S. LTO supply and rig activity. A one percent shock to the oil price is estimated to increase LTO supply and rig activity with 0.3 and 0.8 percent, respectively. A one percent increase in rig activity leads to a 1.7 percent increase in oil production, but also a 0.1 percent increase in costs.
Keywords: Q3; Q4; L71; C32; 330; Oil supply; rig activity; elasticity; tight oil; shale oil; vector error correction models